Association Between Patient Factors and Outcome of Synthetic Cartilage Implant Hemiarthroplasty vs First Metatarsophalangeal Joint Arthrodesis in Advanced Hallux Rigidus. (November 2017) - Goldberg, Andy; Singh, Dishan; Glazebrook, Mark; Blundell, Chris M.; De Vries, Gwyneth; Le, Ian L. D.; Nielsen, Dominic; Pedersen, M. Elizabeth; Sakellariou, Anthony; Solan, Matthew; Younger, Alastair S. E.; Daniels, Timothy R.; et al.
Background: We evaluated data from a clinical trial of first metatarsophalangeal joint (MTPJ1) implant hemiarthroplasty and arthrodesis to determine the association between patient factors and clinical outcomes. Methods: Patients ≥18 years with hallux rigidus grade 2, 3, or 4 were treated with synthetic cartilage implant MTPJ1 hemiarthroplasty or arthrodesis. Pain visual analog scale (VAS), Foot and Ankle Ability Measure (FAAM) sports and activities of daily living (ADL) scores, and Short Form-36 Physical Function (SF-36 PF) subscore were obtained preoperatively, and at 2, 6, 12, 24, 52, and 104 weeks postoperatively. Final outcome data, great toe active dorsiflexion motion, secondary procedures, radiographs, and safety parameters were evaluated for 129 implant hemiarthroplasties and 47 arthrodeses. The composite primary endpoint criteria for clinical success included VAS pain reduction ≥30%, maintenance/improvement in function, no radiographic complications, and no secondary surgical intervention at 24 months. Predictor variables included hallux rigidus grade; gender; age; body mass index (BMI); symptom duration; prior MTPJ1 surgery; preoperative hallux valgus angle, range of motion (ROM), and pain. Two-sided Fisher exact test was used ( P < .05). Results: Patient demographics and baseline outcome measures were similar. Success rates between implant MTPJ1 hemiarthroplasty and arthrodesis were similar ( P > .05) when stratified by hallux rigidus grade, gender, age, BMI, symptom duration, prior MTPJ1 surgery status, and preoperative VAS pain, hallux valgus, and ROM. Conclusion: Synthetic cartilage implant hemiarthroplasty was appropriate for patients with grade 2, 3, or 4 hallux rigidus. Its results in those with associated mild hallux valgus (≤20 degrees) or substantial preoperative stiffness were equivalent to MTPJ1 fusion, irrespective of gender, age, BMI, hallux rigidus grade, preoperative pain or symptom duration. Level of Evidence: Level II, randomized clinical trial.